REVIEW: ANIMAL SERUM REPLACEMENT IN MESENCHYMAL STEM CELLS CULTURE - Ariyani Noviantari; Tati Febrianti (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
ABSTRACT Mesenchymal stem cells (MSCs) are being used in clinical applications and must comply with Good Manufacturing Practices (GMP) standards and The National Agency of Drug and Food Control (NA-DFC)) regulations. MSCs cultured using a culture medium and added with several supplements like animal serums. However, animal serums can be a source of virus transmission. Therefore, it is necessary to substitute supplements for the animal serum that are safe to use in cell therapy using MSCs. The paper discusses substituting animal serum MSCs culture. This paper is a literature review through a literature search in scientific journals and research reports that explains the various studies on free serum in the culture of MSCs. It can be concluded that human platelet lysate (hPL), human platelet-rich plasma (hPRP), human serum (hS), human umbilical cord serum/plasma (hUCS/P), or human plasma-derived supplement for cell culture medium (SCC) can be used as substitutes for animal serum in MSCs culture.   ABSTRAK Terapi menggunakan sel punca mesenkim (SPM) mulai digunakan dalam aplikasi medis dan  harus memenuhi standar Good Manufacturing Practice (GMP) dan aturan serta regulasi dari Badan Pengawas Obat dan Makanan (BPOM). SPM sebaiknya dikultur menggunakan medium kultur ditambahkan suplemen tertentu, misalnya serum hewan. Namun, bahan ini masih mengandung materi hewan yang dapat menjadi sumber transmisi virus. Oleh karena itu diperlukan adanya suplemen pengganti serum hewan yang aman digunakan dalam kultur SPM untuk keperluan terapi sel. Tulisan ini menguraikan tentang bahan pengganti serum dalam kultur SPM. Tulisan ini berupa review literatur yang didapatkan melalui penelusuran pustaka yang didapatkan dari internet. Human platelet lysate (hPL), human platelet-rich plasma (hPRP), human serum (hS), human umbilical cord serum/plasma (hUCS/hUCP), atau human plasma-derived supplement for cell culture medium (SCC) dapat digunakan sebagai pengganti serum pada kultur SPM.